Do Mothers Have Worse Sleep Than Fathers? Sleep Imbalance, Parental Stress, and Relationship Satisfaction in Working Parents - Härdelin G (Dove Medical Press, 2021)
Göran Härdelin,1,2 Benjamin C Holding,1,3 Tim Reess,2 Anahita Geranmayeh,1,2 John Axelsson,1,2 Tina Sundelin1,2 1Department of Clinical Neuroscience, Karolinska Institutet, Stockholm, Sweden; 2Department of Psychology, Stockholm University, Stockholm, Sweden; 3Department of Sociology, University of Copenhagen, Copenhagen, DenmarkCorrespondence: Tina SundelinStress Research Institute, Department of Psychology, Stockholm, 106 91, SwedenEmail tina.sundelin@psychology.su.sePurpose: Previous research indicates that mothers take a larger responsibility for child care during the night and that they have more disturbed sleep than fathers. The purpose of this study was to determine whether such a sleep imbalance exists in working parents of young children, and the extent to which it depends on the way sleep is measured. The study also examined whether imbalanced sleep between parents predicts parental stress and relationship satisfaction.Methods: Sleep was measured for seven consecutive days in 60 parenting couples (average age of the youngest child: 3.3 years ± SD 2.5 years). Actigraphs were worn across the week, and ratings of sleep, parental stress, and relationship satisfaction were made daily.Results: Mothers perceived their sleep quality as worse (b= − 0.38 scale units, p< 0.001), with more wake periods (b= +0.96 awakenings, p< 0.001) but with longer sleep duration (b= +32.4 min, p< 0.01) than fathers. Actigraphy data confirmed that mothers slept longer than fathers (b= +28.03 min, p< 0.001), but no significant differences were found for wake time, number of awakenings or who woke up first during shared awakenings. Furthermore, there was no difference in whether mothers and fathers slept sufficiently. The level of sleep imbalance between parents did not predict parental stress. A larger imbalance in subjective sleep sufficiency predicted decreased relationship satisfaction for fathers (b= − 0.13 scale units, p< 0.01) but increased relationship satisfaction for mothers (b= 0.14 scale units, p< 0.05). No other sleep imbalance measures predicted relationship satisfaction.Conclusion: Our findings are in line with previous research on sleep in men and women in general, with longer sleep and subjective reports of sleep disturbances in women, rather than previous research on sleep in parents of young children. Thus, we found no evidence of a sleep imbalance when both parents have similar working responsibilities.Keywords: parent, sleep, working, parental leave, equal, imbalance